Rompendo fronteiras de gênero: Marias (e) homens na educação física - Helena Altmann (1998)
Aiming to understand how boys and girls construct the gender relations in Physical Education, classes of this subject from four 5th grade groups, breaks and School Olympic Games were observed at a public school in Belo Horizonte, and boys, girls and the teacher were interviewed. Three categories emerged: the occupation of school space, the exclusions in sport games, and the crossing of gender and sexuality borders at school. The observation showed that, in sports, boys controlled more space than girls. However, girls resisted to this domination in various ways, such as by their complicity with the teacher. Exclusions in sport games, one of the main reasons of conflict between girls and boys in these classes, were polarized around gender, although they were not restricted to gender, but were also related to ability, age and strength. There was a simultaneity between being excluded and self exclusion, as well. Within a genderfication of sportive abilities, girls did not represent a challenge to boys, but a threat. Games and plays intermediated and legitimated the relationship between the students, showing the informal circulation of gender and sexuality representation at school. Finally, the relations constructed by girls and boys were characterized by the simultaneous control and crossing of gender borders.